Telomere lengths at birth in trisomies 18 and 21 measured by Q-FISH - Nakamura, Ken-ichi; Ishikawa, Naoshi; Izumiyama, Naotaka; Aida, Junko; Kuroiwa, Mie; Hiraishi, Naoki; Fujiwara, Mutsunori; Nakao, Atsushi; Kawakami, Tadashi; Poon, Steven S.S.; Matsuura, Masaaki; Sawabe, Motoji; et al. (Gene, 2014)
Trisomies 18 and 21 are genetic disorders in which cells possess an extra copy of each of the relevant chromosomes. Individuals with these disorders who survive birth generally have a shortened life expectancy. As telomeres are known to play an important role in the maintenance of genomic integrity by protecting the chromosomal ends, we conducted a study to determine whether there are differences in telomere length at birth between individuals with trisomy and diploidy, and between trisomic chromosomes and normal chromosomes. We examined samples of peripheral blood lymphocytes (PBLs) from 31 live neonates (diploidy: 10, trisomy 18: 10, trisomy 21: 11) and estimated the telomere length of each chromosome arm using Q-FISH. We observed that the telomeres of trisomic chromosomes were neither shorter nor longer than the mean telomere length of chromosomes as a whole among subjects with trisomies 18 and 21 (intra-cell comparison), and we were unable to conclude that there were differences in telomere length between 18 trisomy and diploid subjects, or between 21 trisomy and diploid subjects (inter-individual comparison). Although it has been reported that telomeres are shorter in older individuals with trisomy 21 and show accelerated telomere shortening with age, our data suggest that patients with trisomies 18 and 21 may have comparably sized telomeres. Therefore, it would be advisable for them to avoid lifestyle habits and characteristics such as obesity, cigarette smoking, chronic stress, and alcohol intake, which lead to marked telomere shortening. •The first data of telomere length of 18 and 21 trisomy patients at chromosomal level•The telomere length in trisomies was not significantly shorter than that in controls.•The telomere lengths were very variable within the same cell, and individual at birth.•The telomere of the p-arm was longer than that of the q-arm in 32.3% of the subjects.•No specifically short telomeres on either arm of trisomic chromosomes at birth